Eight keys - LaFleur, Suzanne M. (Yearling, 2012)
Amidst the troubles overtaking her life since she started middle school, Elise finds a new curiosity in the form of a key labeled with her name. Curious as to what the key unlocks, Elise decides to find out and, in the process, discovers the secrets of family and friendship and even begins to learn more about herself.